Advanced synthesis strategies of mesoporous SBA-15 supported catalysts for catalytic reforming applications: a state-of-the-art review - Singh, Sharanjit; Kumar, Ravinder; Setiabudi, H. D.; Nanda, Sonil; Vo, Dai-Viet N. (Elsevier, 2018)
Catalytic deactivation due to agglomeration and metal particle growth has motivated the researchers around the globe to encapsulate the active metal particles into protective shells of mesoporous support. This strategy of encapsulation has emerged as a powerful tool to restrict particle growth thereby improving the catalytic performance, owing to higher accessibility for active sites. In the past decade, various hierarchical mesoporous scaﬀolds with multiple porosities integrated into single structure have been synthesized by considering prototypical SBA-15 support. In this regard, we review the recent developments for designing the SBA-15 support and strategies for encapsulating the metals on to porous inorganic protective shells. An overview of the conventional synthesis techniques, progress and strategies for improving the metal incorporation into these pore channels and its impact on dispersion as well as catalytic properties of SBA-15 supported catalyst are extensively reviewed. Furthermore, a perspective on the challenges and opportunities for resolving the issue of sintering under harsh reforming conditions is substantiated.